Cosmetic injection techniques a text and video guide to neurotoxins and fillers - Kontis, Theda C. (Thieme Publishers, 2019)
The quintessential guide to state-of-the-art cosmetic injection approaches, from two renowned experts! This revised and updated second edition of Cosmetic Injection Techniques: A Text and Video Guide to Neurotoxins and Fillers by esteemed facial plastic surgeons Theda Kontis and Victor Lacombe builds on their bestselling first edition. Content is designed to augment knowledge of beginner injectors and train veteran injectors on how to finesse facial fillers and muscle-relaxing injections. Since publication of the first edition, understanding of the aging face has increased, while the number of